THE FORMATION IN LOCAL AND COLONIAL CULTURES IDENTITY IN ABDULRAZAK GURNAH'S NOVEL "AFTERLIVES" (Karya Ilmiah Mahasiswa (KIMA), 2026)
This study examines the formation of cultural identity through the interaction between local and colonial cultures in Abdulrazak Gurnah’s novel Afterlives. The study is motivated by the need to understand how colonialism influences not only political and economic structures but also the construction of individual and collective identities in postcolonial societies. The objective of this research is to analyze the representation of cultural identity and the forms of postcolonial identity portrayed in the novel. This research employed a qualitative descriptive method using a postcolonial theoretical framework. The primary data source was the novel Afterlives, while secondary data were obtained from books, scholarly articles, and other relevant academic sources. Data were collected through intensive reading, identification of relevant quotations, thematic classification, and qualitative content analysis. The findings reveal that the characters’ identities are shaped by the conflict between local and colonial cultures, resulting in hybrid, ambivalent, and dislocated identities. Colonial experiences create trauma, alienation, and identity crises, while simultaneously encouraging the negotiation and reconstruction of identity. The study demonstrates that identity is a dynamic and ongoing process influenced by historical experiences and cultural encounters. This research contributes to a deeper understanding of the lasting impact of colonialism on cultural identity as represented in postcolonial literature.